Great ape infants’ face touching and its role in social engagement - Beatriz Felicio; Kim A. Bard (Animal Cognition)
Abstract Touch has a key role in the social development of infant primates and in the regulation of social interactions, even so, there’s a rarity of studies on infants’ use of social touch. In this work, we document chimpanzee infants and human infants’ touching of other’s faces, a behavior already described in wild capuchin monkey infants, and investigate possible functions of infants’ social touch. A strength of this study is that we sampled chimpanzee and human infants from three different social ecologies each. Each infant was observed naturalistically, in their everyday environments. In 36 h of observation, we found 269 touch events, specifically 222 face touches and 47 head touches. We found significant differences between groups, within species. Face touching occurred preferentially with adult females in all groups, and preferentially in prosocial contexts, although the most preferred contexts differed across groups. A unifying concept was that almost all infant face touching occurred during joint attention events. We interpret this as the ability of 1-year-olds to use face touching as a behavioral marker of mutual engagement during bouts of triadic connectedness, that is when they engage together with a social partner about an object or an event. In this study, we document an understudied behavior of young chimpanzees and humans, one that is not only part of prosocial interactions, but one that may function to highlight infants’ active role in engagement with another, while they together engage in triadic connectedness.